PENYEDIAAN KETAHANAN PANGAN MELALUI KESADARAN PEMBERIAN ASI DI KECAMATAN PURWOKERTO UTARA KABUPATEN BANYUMAS - Neni Widayaningsih; Barokatuminalloh (Jurnal Ekonomi Bisnis dan Akuntansi (JEBA), 2012)
The purpose of this research is to analyze the society awarenes level of breastfeeding treatment to know how related is eduaction level with breastfeeding treatment awareness , and to know how related is household income with breastfeeding treatment awareness in North Purwokerto Subdistrict. The population in this research is every household that in categories of very poor, poor, and almost poor in North Purwokerto Subdistrict that has babies and toddlers. The sampling technique that is used in this research is Multiple Stages Sampling means samples acquired from the group of population but not all of member of population becomes sample members. Only half of sub-population members become sample members. Total amount of sample acquired in this research is 50. The analysis method in this research used qualitative analysis and tabulation method. The result of the research shows that household food security in North Purwokerto Subdistrict for 72 percents is in secure level, 10 percents in insecure without hunger level, the next 4 percents is in insecure with intermediate hunger level, and 4 percents is in more severe hunger level. The society awareness in the location of research which gave breastfeeding is quite high, which can be seen from how high the percentage of respondents who gave breastfeeding, from available 50 respondents, its 90 percent gave breastfeeding to their babies, both in food secure level and food insecure level withuot hunger or with intermediate or more severe hunger. The duration of breastfeeding treatment by respondent is vary, 50 percents or more for example gave breastfeeding for 2 years, there are also gave breastfeeding for more than 2 years, even up to 3 years, because the babies is still in needs to breastfed and the mothers were still able to produce breastfeeding. The duration of exclusive breastfeeding treatment in majority has conformed with advisable regulation for medical needs which is 6 months. The respondents’ education level in the location of research shows positive trend with breastfeeding treatment awareness and exclusive breastfeeding in every status of food security level. Means that the higher the education level so the knowledge and awareness to give breastfeeding becomes better. The income limit for households to reach food secure level in location of said research is on income >Rp1.100.000/month. The said household income level is related to breastfeeding treatment awareness. The result of research shows that the higher the household income level, the awareness of breastfeeding treatment and exclusive breastfeeding is also better especially in food secure level. The duration of breastfeeding treatment is also better with the increase of household income, because almost every respondent gave breastfeeding 2 for 2 years and exclusive breastfeeding for 6 months, especially on household income level of >Rp1.100.000/month.